Signifikansi Nilai-Nilai Pancasila pada Sila ke Lima Bagi Keadilan dan Kesejahteraan Masyarakat - Yakob Pai Tiba; Yakobus Adi Saingo; I Made Suardana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The country of Indonesia is blessed with great natural wealth so that every citizen should be able to enjoy prosperity, but the facts show that there are still many members of society who are detected as still living below the poverty line. The main objective is to review the significance of Pancasila values ​​in the fifth principle for justice and social welfare. The method used in this research is a literature study with a descriptive analytical approach, the results of which reveal that even though Pancasila as the basis of the Indonesian state emphasizes the importance of social justice, the practice of social justice in the field still faces various significant challenges. This research reveals that there is striking inequality in various aspects of people's lives, including access to the economy, education, health and infrastructure. Even though various policies have been implemented, the results often do not meet expectations, resulting in inequality that continues to widen. Therefore, more inclusive and sustainable policy reforms are needed to overcome social injustice. Some concrete steps that can be taken include fair economic redistribution, increasing access to education and health services, and equitable infrastructure development. All of these efforts must be carried out by involving community participation to ensure that the policies implemented truly reflect the needs and aspirations of all levels of society.